Evidence of Deep DOC Enrichment via Particle Export Beneath Subarctic and Northern Subtropical Fronts in the North Pacific - Lopez, Chelsea Nicole; Hansell, Dennis Arthur (Frontiers in Marine Science, 2021)
Here we provide compelling evidence that deep particle export enhanced dissolved organic carbon (DOC) concentrations beneath the Pacific’s Subarctic Front (SA, 42ºN) and Northern Subtropical Front (NST, 34ºN). We report three main findings: First, deep export of subjectively small particles (128-512 µm) was apparent throughout the frontal zone in which the SA resides. However, export of large particles was specifically associated with the SA, rather than the entire frontal zone, and appeared to exclusively transfer DOC into the bathypelagic water column. Second, a similar DOC enrichment existed beneath the NST, though this signal was curiously not accompanied by observable particles (>128 µm). We conclude that export occurring previously in winter left this DOC behind as a residue, though the associated particles were no longer present by spring. Third, the presence of strong hydrographic fronts was not the only control on export that resulted in these unique DOC distributions. Deep export and DOC enrichment was also controlled by latitude-specific biogeochemical and hydrographic conditions, such as depth of the nutricline and seasonal mixed layer shoaling. Given these observations, the fronts within the transitional region of the North Pacific are clearly special locations for deep carbon sequestration and for providing uncommon DOC enrichment that ultimately supports the deep microbial community.